Novel cross-linked PBI-blended membranes evaluated for high temperature fuel cell application and SO2 electrolysis. (2018) - Peach, Retha; Krieg, Henning M.; Krüger, Andries J.; Bessarabov, Dmitri; Kerres, Jochen
Abstract: Within this study various partially fluorinated polyaromatic and PBI blend components were covalent-ionically cross-linked to obtain acid and base-excess proton exchange membranes that can be applied in high temperature fuel cells and SO2 electrolysis. A stability assessment of the blend membranes included an extraction experiment in the organic solvent N, N-dimethylacetamide (DMAc), Fenton's Test (FT) and an 80 wt% H2 SO4 treatment for 120 hours at 100 °C. Furthermore the thermal stability of the materials were evaluated by TGA-FTIR coupling, and the H + -conductivity determined for the phosphoric acid-doped (PA) membranes in temperature ranges 60-140 °C. It was found that all blend membranes showed good chemical stability during the H2 SO4 treatment; though the base-excess blend membranes reported better chemical stabilities in the FT and DMAc extraction experiments in comparison to the acid-excess blends. The earliest thermal degradation for a blend membrane was found to start at 277 °C, only after the H2 SO4 treatment, supporting the thermal stability. For the PA-doped blend membranes conductivities of 39, 6 mS/cm reported at 140 °C was comparable to earlier work on similar membrane blends, but now achieved at a lower PA-doping level. Furthermore the base-excess membrane selected for fuel cell (FC) testing reported comparable in the polarization curves recorded at 140 ⁰C, however a maximum power density of 88.2 mW/cm 2 was reached in comparison to the 72.8 mW/cm 2 of Celtec®-P under the same operation conditions for similarly prepared MEAs. This all proves promising for further testing and optimization of the blend membranes for HTFC and SO2 electrolysis applications.